NEUROLOGIC MANIFESTATION AND PERICARDIAL EFFUSION UNVEILING AN AUTOIMMUNE HYPOTHYROIDISM - Chong, Shu May; Lim, Lay Ang (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Autoimmune hypothyroidism is an antibody-mediated chronic inflammatory process. Thyroid destruction may be intermittent. Given its chronic and progressive nature, the diagnosis is often challenging since the exhibited signs and symptoms are often subtle and non-specific. We report a middle-aged male with bilateral upper and lower limb weakness and pericardial effusion. Investigation led to a diagnosis of autoimmune hypothyroidism. CASE A 64-year-old male presented with a two-week history of lethargy, poor appetite, and lower limb swelling. Initially, he was treated for pneumonia and cardiac failure due to chest radiography showing obscured cardio-phrenic angle. Further history revealed he had inability to walk for one year due to bilateral lower limb weakness. He had proximal muscle weakness of all four limbs. Sensation and reflexes were preserved in the upper limbs but absent in the lower limbs. His nerve conduction study and electromyography revealed myopathic changes involving all four extremities with absent neurosensory responses in both lower extremities. His cranial CT scan showed bifronto-temporal subdural effusion while his echocardiography exhibited pericardial effusion with cardiomegaly. His thyroid function tests revealed profound hypothyroidism (TSH>100, fT4 <1). Together with the presence of markedly raised anti-TPO antibodies, he was diagnosed to have autoimmune primary hypothyroidism. He also had normocytic normochromic anaemia and hypercholesterolemia consistent with severe hypothyroidism. He was eventually started on oral L-thyroxine (1.6 mcg/kg/day). CONCLUSION This case report highlights the potential for severe neuromuscular and cardiovascular consequences due to untreated chronic autoimmune hypothyroidism. Thyroid dysfunction is a consideration in a patient with neurologic manifestation. Early diagnosis and prompt treatment of hypothyroidism can potentially avert long-term hypothyroid sequelae.